An investigation of the utilisation of condoms among patients on antiretroviral therapy at Aliwal North Hospital as a prevention method against HIV re-infection - Sandlana, Simphiwe Dennis (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil)--University of Stellenbosch, 2011.